Extensive Early Marine Seafloor Cementation in a Modern Epeiric Sea Induced by Seawater Properties and a Shallow Redox Boundary Below the Seafloor - Y. Ge (Geochemistry, Geophysics, Geosystems)
Abstract Extensive early marine cementation at the seafloor has important environmental implications (e.g., ocean chemistry and atmosphere pCO2), but its driver remains controversial, because many factors have been proposed to affect early marine cementation. At the Abu Dhabi coastal area of the Persian Gulf, extensive early marine cementation at the seafloor provides a good modern study case for ancient analogs. Based on petrological (thin section, cathodoluminescence and scanning electron microscope) and geochemical (e.g., δ13CDIC, alkalinity, aragonite saturation) analyses, this study investigates integrated factors from seawater to sediment properties and tests previously proposed explanations about extensive early marine cementation at the seafloor. Results suggest multiple factors involved in the early marine cementation. CaCO3 saturation, small CaCO3 saturation gradient and higher sea level in the early Holocene are consistent with former explanations. A new finding is shallow redox boundary within the seafloor sediment promoting extensive early marine cementation. The formation of shallow redox boundary is unrelated to anoxic bottom water and/or enhanced organic influx, but rather is related to: (a) high salinity under hot and arid climate, and (b) low‐energy and restricted shallow marine settings., These conditions undoubtedly occurred in past shallow and warm epeiric marine seas. This provides new insights into formation mechanism and paleoenvironmental interpretation of ancient extensive early marine cementation at the seafloor on epeiric seas.